2020
DOI: 10.21776/ub.ijds.2020.007.02.15
|View full text |Cite
|
Sign up to set email alerts
|

Education Budget Politics: Is It Pro-Disabilities? Case of Yogyakarta Municipality, Indonesia

Abstract: This article aims to examine the education budget policy allocated for inclusive education programs, wherein providing a budget is highlights. In this context, Yogyakarta City government is submit because of its embracement unto inclusive budget post for education. This paper used a qualitative approach with document-analysis method to analyze the inclusive education budgets from 2017 to 2019. The research findings are; first, the budget allocation for inclusive education is considering to be minimal when comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…On the other hand, the two regions in 2018 allocated an education budget far below the national education budget policy standard, which shows that the two regional governments have not had a grand design of sustainable education policy yet so that in the end it affects the failure of the 20% budget policy implementation. A number of previous studies have also revealed that the grand design of the education budget policies needs to be well-formulated, followed by a high commitment from the local governments to realize them through supportive budget policies (Rahmat et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the two regions in 2018 allocated an education budget far below the national education budget policy standard, which shows that the two regional governments have not had a grand design of sustainable education policy yet so that in the end it affects the failure of the 20% budget policy implementation. A number of previous studies have also revealed that the grand design of the education budget policies needs to be well-formulated, followed by a high commitment from the local governments to realize them through supportive budget policies (Rahmat et al 2020).…”
Section: Discussionmentioning
confidence: 99%